A survey of customer satisfaction towards quality of bus transportation services in Kuching City / Angelina Sigang Apui ... [et.al] - Apui, Angelina Sigang; Grunsin, Evelyn; Philip, Ferdinand; Lah, Kathy Mujan (2004)
This study, “ A Survey of Customer Satisfaction Towards Quality of Bus Transportation Services in Kuching City” is done due to the requirement of PAD340 subject. Customer satisfaction here refers to the public or customers’ satisfaction delivered by the bus transportation services in the Kuching City. The purpose of this research is to see whether the passengers are satisfied or not with the service provided. Meaning that, the passengers will be the respondent of this study. Here also, this study is done to identify the reasons that are mostly influence customers’ satisfaction. This study has been conducted through questionnaire distributed to respondents. The interview also has been conducted to gain the insight opinion of the company who handle the transportation services. The observations also have been done to get the real fact of the bus condition. The finally indicate the factors that influence that contributing to the passengers satisfaction. Lastly, the recommendations are made based on the findings of the study as to improve the passengers’ satisfaction of government sector towards the transportation services in Kuching City.